Efficacy of 6‐mm diameter fully covered self‐expandable metallic stents in preoperative biliary drainage for pancreatic ductal adenocarcinoma. Issue 1 (8th September 2021) - Kataoka, Fumiya; Inoue, Dai; Watanabe, Masato; Fukuda, Keita; Nobusawa, Tsubasa; Umemura, Kayo; Miura, Natsuki; Yokota, Takuya; Yoshioka, Astushi; Shimoji, Kohei; Nakazono, Ayano; Horike, Hideyuki; et al.
Abstract: Objectives: Plastic stents (PS) used for preoperative biliary drainage (PBD) of pancreatic ductal adenocarcinomas (PDAC) tend to be associated with a high incidence of recurrent biliary obstruction (RBO). Although 10‐mm diameter fully covered self‐expanding metallic stents (FCSEMS) have come into use, vigilance is still required to prevent complications, such as cholecystitis and surgical site infection. The present study examined the efficacy and safety of the 6‐mm diameter FCSEMS for PBD. Methods: The present retrospective study compared the incidence of complications associated with the use of 6‐mm FCSEMS and PS. The inclusion criteria were a diagnosis of PDAC and preoperative endoscopic biliary tract drainage performed at our institution between April 2012 and June 2019. Results: Of the 51 patients enrolled, 25 and 26 patients received a PS and a 6‐mm FCSEMS, respectively. The RBO incidence was significantly lower in the 6‐mm FCSEMS group (7.7%) than in the PS group (40.0%) ( p = 0.009), and time to RBO was significantly longer in the 6‐mm FCSEMS group (HR = 6.008, p = 0.021). The patency rate at three months after stent placement was significantly higher in the latter group (83.5% vs. 45.3%, p = 0.009, Log‐rank test). The groups did not differ significantly in terms of complications associated with PBD, such as cholecystitis and surgical site infection. Conclusion: The present findings suggested that the 6‐mm FCSEMS may be an effective drainage device for use in PBD in PDAC treatment.